Protecting/preventing cosmetic injurious effects induced by UVA radiation on skin of subject, comprises administering agent to inhibit transcription factor hypoxia-inducible factor-1 alpha, where agent is e.g. antibody or its fragment - BERNERD FRANCOISE; MARIONNET CLAIRE; KRUTMANN JEAN (2010)
Protecting or preventing cosmetic injurious effects induced by UVA radiation on the skin of a subject, comprises administering an agent for inhibiting the transcription factor hypoxia-inducible factor-1 (HIF1) alpha or its expression, where the agent is an antibody or its fragment, a molecule comprising RNA interference (RNAi) sequence, and antisense RNA or a molecule of flavonoid family. Independent claims are included for: (1) the agent capable of inhibiting the transcription factor HIF1 or its expression, for a therapeutic use in the protection or prevention of injurious effects induced by UVA radiation on the skin, or the agent which is an antibody or antibody fragment, the molecule comprising a sequence of RNAi, antisense RNA or a molecule of the flavonoid family; (2) in vitro screening of the agents capable of ensuring the prevention or protection of the skin having injurious effects induced by UVA radiation, comprising (a) contacting the agents for screening with dermal fibroblasts, (b) irradiating the fibroblasts with UVA radiation, (c) determining the expression level of HIF1 protein in the fibroblasts with respect to its expression in dermal fibroblasts which is not contacted with the agent, allowing the identification of an agent for cosmetic or therapeutic use in dermatology; and (3) in vitro evaluation of efficiency of an agent for preventing or protecting the skin against injurious effects induced by UVA radiation, comprising contacting the agent with dermal fibroblasts, irradiating the fibroblasts with UVA radiation, and determining the expression level of HIF1 protein in the fibroblasts with respect to its expression in dermal fibroblasts which is not contacted with the agent; (4) evaluating the efficiency of the agent in the prevention or the protection of the skin having the injurious effects induced by UVA radiation, comprising determining the level of expression of the transcription factor HIF1 in fibroblasts in a sample from a skin of a subject exposed to UVA after contacting with the agent, and comparing the level determined in the determining step at the level of expression of HIF1 in fibroblasts in a sample from a subject exposed to UVA in the absence of the agent; and (5) determining the impact of sun exposure on the skin of the subject, comprising determining the level of expression of the transcription factor HIF1 in fibroblasts in a sample from the subject's skin which is not exposed, and comparing the level determined in determining the expression level of HIF1 in dermal fibroblasts which is not subjected to sun exposure. ACTIVITY : Dermatological; Cytostatic. MECHANISM OF ACTION : HIF1alpha transcription factor inhibitor. La présente invention concerne différentes méthodes de protection ou de prévention des effets délétères cosmétiques induits par le rayonnement UVA sur la peau d'un sujet, comprenant l'administration d'un agent capable d'inhiber le facteur de transcription HIF1α ou son expression. La présente invention concerne également des applications thérapeutiques d'un agent capable d'inhiber le facteur de transcription HIF1α ou son expression, dans la photoprotection de la peau contre le rayonnement UVA. Enfin, l'invention a également trait à des procédés pour cribler des molécules susceptibles d'assurer la protection et/ou la prévention des dommages induits par le rayonnement UVA ainsi que des méthodes d'évaluation de l'efficacité de molécules dans leur action protectrice de la peau à l'encontre du rayonnement UVA.